Advanced Foreign Experiences In Attracting Foreign Direct Investment - Ochilov Bobur Bakhtiyor ugli (Periodica Journal, 2025)
This article describes the role and importance of the country’s investment attractiveness in attracting foreign direct investment, as well as the necessary mechanisms for attracting investment, and studies the opinions of foreign and domestic economists on this topic. The article also analyzes the indicators of foreign direct investment in developed countries. In particular, the investment position of the USA, China, Singapore and Germany is studied. At the same time, as a result of studying advanced foreign experiences, scientific conclusions and recommendations are formulated on increasing the investment attractiveness of the Republic of Uzbekistan.
Keywords: investment attractiveness; foreign investment; investment potential